Simulation Analysis of New Symmetric/Asymmetric Type Multilevel Inverter Topology - Thiyagarajan V (International Journal of Advanced Science and Technology, 2020)
Multilevel inverters can synthesize a high output voltage staircase waveform using much lower rated switches. This article proposes a new inverter topology with least number of switching devices. The proposed inverter comprises of four sources and ten switches to create higher output levels. This topology can be worked with equal and unequal voltage magnitudes. To prove the superiority of the proposed topology, the comparison study is performed with other existing topologies based on various performance indices. To exhibit the operation and overall performance of the proposed topology, the simulation results are presented for 9-level, 17-level and 25-level inverter operations.